Bundle-branch reentrant tachycardia - Tomé, Helbert Pereira (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Although the bundle-branch reentrant tachycardia was described about 30 years ago, it is unknown to many cardiologists, and at times it is not identified by electrophysiologists. Probably underdiagnosed, especially in patients with dilated cardiomyopathy, this entity affects patients with lesion of the infra-His system. Identifying this arrhythmia is important to enable curative treatment, decrease the need for antiarrhythmics and minimize appropriate therapies after the implant of an implantable cardiac defibrillator.